PERAN DINAS KOMUNIKASI DAN INFORMASI KABUPATEN INDRAGIRI HILIR DALAM PUBLIKASI INFORMASI PUBLIK TAHUN 2016-2017 - Mawarni "; Muchid " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Abstrct               Public information is information that is produced, stored, managed, sent, and or received by a public body relating to the administration of the state and / or the organizer and administration of other public bodies in accordance with this Law and other information relating to the public interest, as with this research intended to find out How the Role of the Office of Communication and Information in Public Information Publication, the purpose of this study is to describe the Role of the Office of Communication and Information in Public Information Publication. The results of this study are that the role of the Office of Communication and Information of Indragiri Hilir Regency in the Public Information Publication of 2016-2017 is performed less than optimal where in the role indicators namely the coordinator, facilitator, stimulator have been running poorly, which in each of these indicators the government has provided services which is needed by the public in fulfilling public information but is still accompanied by several obstacles and problems.Keywords: E-Government, Public Relations, Public Information